OCORRÊNCIA DOS GENÓTIPOS G E P DE ROTAVÍRUS DO GRUPO A EM BEZERROS DE REBANHOS DE CORTE NO ESTADO DE SÃO PAULO, BRASIL - Buzinaro, M.g. [UNESP]; Samara, S.i. [UNESP]; Pereira, E.a.s.; Fuentes, D.b. [UNESP]; Oliveira, M.c.s. (Instituto Biológico, 2021)
The frequency of group A rotavirus and the molecular G and P characterization of strains in beef cattle were determined from July 2003 to July 2004, in herds of the state of São Paulo, Brazil. Samples came from 649 calves, aged between 1 and 60 days, from 14 beef cattle herds, regardless of clinical manifestation of diarrhea. A 64.3% (9/14) frequency of rotavirus among herds and 6.2% (40/649) among animals were detected by ELISA and polyacrylamide gel electrophoresis (PAGE). The higher frequency infection was detected in animals aged between 16 and 30 days (10.5%). Rotavirus infection was diagnosed in animals with (25.8%; 22/85) or without (3.2%; 18/564) clinical signs of diarrhea. A correlation was found between the presence of infection and the clinical manifestation of diarrhea (p < 0.05). PAGE analysis of the rotavirus’s genome profile identified 7 distinct electropherotypes which indicated extensive genomic diversity of the rotavirus in the region under analysis. Genotyping by polymerase chain reaction (RT-PCR) of the rotavirus strains revealed the genotypes G6P[5], G6P[11], G6P[5]P[11] and G10P[11].

Foi determinada a ocorrência de rotavírus do grupo A e a caracterização molecular G e P de estirpes detectadas em bezerros de rebanhos de corte em propriedades rurais do Estado de São Paulo, Brasil. Foram analisadas amostras de fezes de 649 bezerros de 14 rebanhos de corte com idade entre 1 e 60 dias, independentemente da manifestação clínica de diarréia, colhidas de julho de 2003 a julho de 2004. Por meio das técnicas de ELISA e de eletroforese em gel de poliacrilamida (PAGE), determinou-se a ocorrência de rotavírus do grupo A em 64,3% (09/14) dos rebanhos e em 6,2% (40/649) dos animais. A maior freqüência de infecção foi detectada em animais com idade entre 16 e 30 dias (10,5%). Foram diagnosticados bezerros infectados por rotavírus tanto em animais com sinais clínicos de diarréia (25,8%; 22/85) quanto naqueles assintomáticos (3,2%; 18/ 564), existindo, porém, uma correlação entre a presença da infecção e a manifestação clínica da diarréia (p < 0,01). A análise do perfil do genoma do rotavírus por PAGE identificou sete eletroferótipos distintos, indicando grande diversidade genômica dos rotavírus na região estudada. A genotipagem pela reação em cadeia da polimerase (RT-PCR) das amostras de rotavírus revelou que as estirpes circulantes nos rebanhos eram G6P[5], G6P[11], G6P[5]P[11] e G10P[11].
OCCURRENCE OF THE GENOTYPES G AND P OF GROUP A ROTAVIRUS IN CALVES IN BEEF HERDS IN THE STATE OF SÃO PAULO, BRAZIL
Keywords: Rotavirus; cattle; diarrhea; RT-PCR; genotypes P; genotypes G; Rotavírus; bovino; diarréia; RT-PCR; genótipos P; genótipos G